Evaluation of Village Fund Allocation Management - Parera, Viki; Silooy, Revi Wilhelmina; Usmany, Alfrin Ernest Marten (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to evaluate the management of Village Fund allocation in Wamkana Village, Namrole District, South Buru Regency. The formulation of the problem includes planning, budgeting, implementation, reporting, administration, accountability, and evaluation. The method used is descriptive qualitative with the object of research in Wamkana Village. Data sources consist of primary data through interviews with the village government and community, as well as secondary data from related village documents. The results of the study indicate that the planning of village fund allocation has not been maximized, while budgeting does not provide enough open space for the community. The implementation of the program is good, but financial reporting is not in accordance with Permendagri No. 20 of 2018. Administration is still done manually, which is quite good, but the accountability and evaluation of the village government seem closed and have never been done. This shows the need to increase transparency and community participation in the management of village funds.